2020
DOI: 10.7150/thno.47239
|View full text |Cite|
|
Sign up to set email alerts
|

circPTCH1 promotes invasion and metastasis in renal cell carcinoma via regulating miR-485-5p/MMP14 axis

Abstract: Background: Circular RNAs (circRNAs) are a new class of non-coding RNAs (ncRNAs) that are derived from exons or introns by special selective shearing. circRNAs have been shown to play critical roles in various human cancers. However, their roles in renal cell carcinoma (RCC) and the underlying mechanisms remain largely unknown. Methods: A novel circRNA-circPTCH1, was identified from a microarray analysis of five paired RCC tissues. Then, we validated its expression and charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 52 publications
1
36
0
Order By: Relevance
“…Based on accumulating evidence, the most explored function of circRNAs is regulating gene expression through ´sponging´ other gene expression regulators, in particular miRNA 33 . For example, circPTCH1 could act as a sponge for miR-485-5p to promote invasion and metastasis in renal cell carcinoma 34 . Hsa_circ_0000326 interacted with miR-338-3p to facilitate lung adenocarcinoma progression 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on accumulating evidence, the most explored function of circRNAs is regulating gene expression through ´sponging´ other gene expression regulators, in particular miRNA 33 . For example, circPTCH1 could act as a sponge for miR-485-5p to promote invasion and metastasis in renal cell carcinoma 34 . Hsa_circ_0000326 interacted with miR-338-3p to facilitate lung adenocarcinoma progression 35 .…”
Section: Discussionmentioning
confidence: 99%
“…It showed that AhR expression was abnormally increased in RCC. RCC was often accompanied by EMT conversion ( 16 ). We next detected the expression of E-cadherin, N-cadherin, and Vimentin related to EMT.…”
Section: Resultsmentioning
confidence: 99%
“…It showed that AhR expression was abnormally increased in RCC. RCC was often accompanied by EMT conversion (16). We next detected the 1C,D).…”
Section: High Expression Of Ahr In Rcc Tissuesmentioning
confidence: 93%
“…Based on accumulating evidence, the most explored function of circRNAs is regulating gene expression through ´sponge´ other gene expression regulators, in particular miRNA [32]. For example, circPTCH1 could act as sponge for miR-485-5p to promote invasion and metastasis in renal cell carcinoma [33].…”
Section: Discussionmentioning
confidence: 99%